PENERAPAN PSAK 1 DALAM PENYUSUNAN LAPORAN KEUANGAN: STUDI PADA PERUSAHAAN PERTAMBANGAN ENERGI YANG TERDAFTAR DI BEI - Ghina Kemala Dewi; Ashar Basyir; Dini Andriyani; Rizki Muti Agustiani (Jurnal Aplikasi Perpajakan, 2025)
PSAK 01 is an accounting standard that regulates the presentation of financial statements. The conformity of financial statements with PSAK can demonstrate a company's credibility and influence decision-making by various parties. The purpose of this study was to determine the presentation of financial statements in energy mining companies and their compliance with PSAK No. 1. This study employed qualitative research using purposive sampling to determine the sample, and 10 companies were selected. Data were obtained from the financial statements of energy mining companies. This study evaluated the financial statements of energy mining companies, beginning with a comparative analysis of the research subjects using the concept of comparability in terms of accounting policies and financial statement presentation. Then, it was adjusted and compared between the financial statements of energy mining companies and PSAK No. 1 concerning the Presentation of Financial Statements. Based on the discussion and research results, it can be concluded that the financial statements presented by energy mining companies are in accordance with PSAK 1. However, they do not include information regarding dividend distribution to shareholders.